2019
DOI: 10.1111/pirs.12381
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of urban sprawl in urban areas of Iran

Abstract: During the recent decades, debates about urban sprawl have increased strongly in Iran. Literature review shows that there are few studies about causes of sprawl in urban areas of Iran. This paper analyses driving forces in creation or intensification of urban sprawl in Iranian cities. The methodology of the research is based on documentary and survey method. Results indicate that the most important drivers of urban sprawl are 22 factors in Iran. By using exploratory factor analysis, 22 factors are summarized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…While urban agglomeration is a highly developed spatial form of integrated cities (Fang & Yu, 2017), urban sprawl mostly occurred in lower densities accompanied by expansion of urban periphery, is acknowledged as the opposite force, with its character of scattered and leapfrogging development (Mills 1981;Brueckner & Fansler 1983;Lowry, 1988;Hayden, 2004;Downs, 1999;Ewing, 2008;Ahyuni & Nur, 2020). Though urban sprawl is a global phenomenon, but it is always viewed in different ways on how and why it was resulted (Hosseini & Hajilou, 2019;Abulibdeh et al, 2019).…”
Section: Conceptualizing Of Urban Sprawlmentioning
confidence: 99%
“…While urban agglomeration is a highly developed spatial form of integrated cities (Fang & Yu, 2017), urban sprawl mostly occurred in lower densities accompanied by expansion of urban periphery, is acknowledged as the opposite force, with its character of scattered and leapfrogging development (Mills 1981;Brueckner & Fansler 1983;Lowry, 1988;Hayden, 2004;Downs, 1999;Ewing, 2008;Ahyuni & Nur, 2020). Though urban sprawl is a global phenomenon, but it is always viewed in different ways on how and why it was resulted (Hosseini & Hajilou, 2019;Abulibdeh et al, 2019).…”
Section: Conceptualizing Of Urban Sprawlmentioning
confidence: 99%
“…Defined by its repercussion of uncontrolled growth Several instances of literature are definite that uncontrolled or unrestrained urban growth is largely blamed for the occurrence of urban sprawl. Hosseini and Hajilou (2019) refers to urban sprawl as an outgrowth of unrestrained urban growth, with consequences that are mostly present outside urban peripheries, alongside highways connecting other cities or satellite urban centers. Planners and planning authorities are to blame for incompetence in integrated policy planning and poor decision making.…”
Section: Its Consequences To Socio-environmentmentioning
confidence: 99%
“…Hence, rapid population growth not only turn out to be the main component of sprawl but is also responsible for environmental change and resource depletion. Hosseini and Hajilou (2019) claims overpopulation can cause cities to suffer from quality reduction in public amenities, overcrowded services delivery, and a decreased quality of life. The consequences of overpopulation in cities create pressure on growing spatial expansion and urban sprawl.…”
Section: B Institutionalmentioning
confidence: 99%
“…Iran, as an important developing country in the Middle East, has witnessed urban sprawl over the past few decades. Hosseini et al (2019) showed that 36% of the urban spatial expansion in Iran is the result of sprawl in cities between 1986 and 2011 [57]. The observations on urban sprawl in Iran show that this phenomenon has an outward trend in different city sizes, from metropolitan areas and large cities like Tehran [58] and Qom [59] to mid-sized and small cities like Yazd [60] and Kazerun [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The observations on urban sprawl in Iran show that this phenomenon has an outward trend in different city sizes, from metropolitan areas and large cities like Tehran [58] and Qom [59] to mid-sized and small cities like Yazd [60] and Kazerun [29]. Several studies investigated factors influencing the urban sprawling of the Iranian cities, including rapid urbanization, inefficient urban planning system, and weaknesses of master plans, modernization, improvement of technology, land speculation, economic forces, and public construction [24,28,57,61]. The boom in urban population is driven by natural population growth and the increased rate of immigration from rural areas to the cities, which leads to the failure of the rural areas in serving their traditional functions in the settlement system of Iran.…”
Section: Literature Reviewmentioning
confidence: 99%